Analisis Pemanfaatan Teknik Serangan DDOS pada Mikrotik Cloud dan Melakukan upaya penangannya - Syahendra Surya; Tengku Mohd Diansyah; Risko liza (SNASTIKOM, 2023)
Internet services have many benefits and are widely used, but also have disadvantages that can be utilized by hackers to carry out attacks such as DDoS. One solution to manage and control internet networks is to use MikroTik CHR (Cloud Hosted Router), a virtual router solution provided by MikroTik. CHR is designed to run on various virtualization platforms such as VMware, VirtualBox, Hyper-V, and Clouds such as Amazon Web Services, Google Cloud Platform, and Microsoft Azure.This research aims to analyze DDoS attack techniques used and implemented on the MikroTik CHR platform and the security effort strategies that can be used to protect MikroTik CHR from DDoS attacks that can cause service disruptions and financial losses and their handling. This research only focuses on DDoS attacks on MikroTik CHR and security strategies that can protect it from attacks. The results show that some effective security strategies include configuring firewalls, enabling protection features, and performing regular monitoring and software updates. In conclusion, the MikroTik CHR can be protected from DDoS attacks with proper security strategies, and it is necessary to pay attention to strict security monitoring, software updates, and an integrated and comprehensive security strategy to protect the MikroTik CHR from DDoS attacks.